Kinetics of Induction of the Lactose Operon on an Episome in Salmonella typhimurium - Ballesteros-Olmo, A. (1969)
A kinetic study of induction of the enzymes of the lactose operon was carried out under conditions known to affect the kinetics of derepression of the enzymes of the histidine operon. The results show that the lactose system is similar to the histidine system in its responsiveness to conditions thought to affect the formylating capacity of the cell. This was demonstrated in the following ways: (i) trimethoprim, which is known to reduce the formylating capacity of the cell, gives rise to a relatively long interval between the times of induction of β-galactosidase and transacetylase; (ii) under conditions in which the histidine operon is derepressed, chloramphenicol causes a prolongation of the interval between the times of induction of the two enzymes, and this prolongation is reversed by adenine, methionine, and serine, compounds known to enrich the one-carbon pool of the cell; and (iii) 4-amino-5-imidazolcarboxamide ribonucleoside, a compound which may act as a drain for formyl groups, reverses the effect of the latter compounds. The finding that the interval between the times of induction of the two enzymes is shortened under conditions expected to maintain a relatively high intracellular fo rmylating capacity suggests that under certain conditions translation of the polycistronic messenger ribonucleic acid of the lactose operon may be initiated at more than one site or may proceed more rapidly from the operator end.